(untitled) (International Seven Journal of Multidisciplinary, 2025)
A ranula is a pseudocyst resulting from mucous extravasation secondary to damage of the sublingual gland, showing variability in its growth rate and a high recurrence rate. The lack of consensus regarding a standard treatment stems from the diversity of clinical presentations and the range of available surgical techniques. The complex anatomy of the sublingual gland plays a decisive role in the formation of the ranula, which can be classified as oral, plunging, or mixed. Diagnosis is based on clinical examination and may be complemented by imaging exams, especially for plunging ranulas. Therapeutic modalities include conservative and surgical approaches, with micromarsupialization recommended for oral ranulas and radical excision of the sublingual gland being the most effective technique for recurrent or plunging cases. It is concluded that therapeutic choice should consider lesion extent, risk of recurrence, and the anatomical characteristics involved.